Using social semiotics and variation theory to analyse learning challenges in physics: a methodological case study. (14th October 2020) - Eriksson, Moa; Eriksson, Urban; Linder, Cedric
Abstract: The aim of the paper is to create a way of extending the utility of using variation theory of learning (VTL) as an analytic tool for exploring student learning in interactive environments for highly complex disciplines such as physics that aims at obtaining additional insights and understanding of students' learning challenges in physics drawing on a phenomenography perspective. To do this we propose an analytical combination of two perspectives—social semiotics and the VTL—using theoretical constructs from both. Here, in keeping with the phenomenographic perspective that underlies VTL, learning is taken to mean coming to experience things in distinctly new ways. As a case study, students were video recorded during a group problem-solving session while working on circular motion tutorial problems. Through the combined analytic approach, we were able to identify the students' relevance structure as enacted as a function of what was in focal awareness and what dimensions of variation that were presented. A social semiotic multimodal transcription is used to illustrate the proposed methodology, which is made up of the semiotic systems that the students chose to use to build their discursive engagement on. As a methodology paper, and because such discussion already exists in the literature, how this kind of analytic combination can provide additional teaching insights and how these insights could be used to enhance teachers' understanding of their students' learning are not presented in this paper.